Process Evaluation and In-vitro Drug Release Study of Fast Dissolving Uncoated Tablets of Drotaverine HCl - Kumar, Deovrat; Kumar, Amit; Malik, Jitender K; Semwal, Pooja (European Journal of Scientific Exploration, 2019)
Drotaverine, a selective phosphodiesterase (PDE) isoenzyme IV inhibitor. It has been found to be useful in spastic and motility disorders of the smooth muscle in adult. In the present work an attempt was made to study the screening of critical processing parameters affecting the dissolution profile of Drotaverine HCl. For Drotaverine HCl Lubrication time, milling time, and blending time was found to be effective parameter. Compression speed and compression force is also having effect on dissolution of Drotaverine HCl. The in-vitro drug release was carried out on the formulated tablet and compared with the marketed product.